IgA-protease activity coupled to cellular enzymes of different Streptococcus pneumonia serotypes isolated in pediatric bacteria carriers - A. Z. Zaripova (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Streptococcus pneumoniae are significant causative agents of severe and life-threatening acute pneumonia, meningitis, as well as otitis and sinusitis both in children and elderly. As many as 1.2 million pediatric lethal outcomes due to pneumonia and infections of the central nervous system (meningitis) caused by S. pneumoniae, are recorded worldwide annually, a large proportion of which occur in developing countries. Metal-dependent IgA1 proteases derived from pathogenic bacteria comprise an important group of bacterial enzymes cleaving human immunoglobulin A1 (IgA1) at the hinge region, thereby interfering with fully-executed host antibacterial immunity.Objective. To study activity of IgA1proteinases and their class profile (Na2-EDTA and PMSF-inhibited) in various pneumococcal serotypes isolated from nasopharyngeal carrier children.Materials and methods. There were examined 585 children attending preschool facilities residing in Kazan (n = 331) and rural areas (n = 254). Microbiological, molecular genetics and immunochemical methods were used to identify, serotyping composition and protease activity of Streptococcus pneumoniae isolates. Data statistical processing was carried out by using software Graph Pad Prism version 5.0.Results. Prevalence of S. pneumonie in pediatric carriers aged 1.5–3 years was 35.1%, 3–5 years — 23.4%, 5–7 years — 19.6%, and over 7 years — 21.9%. Vaccine serotypes 14, 19F, 23F as a part of current pneumococcal vaccines (Prevenar, Pneumavax-23) comprised as high as 55.8%. However, in 19% of cases were positive for non-vaccine S. pneumoniae strains. Non-typeable strains were detected in 5.8% isolates. IgA-proteinase activity was detected in cell lysates of 45 (86.5%) S. pneumoniae strains isolated from pediatric carriers. Cell lysates of S. pneumoniae strains showing no proteolytic properties, were assigned to serotypes 12F, Sg18. Thus, studies on development of alternative vaccines containing immunogenic proteins, adhesins or other virulence factors common to capsulated and non-typeable (encapsulated) pneumococcal strains hold promise. All the aforementioned accounts for a need for microbiological monitoring of S. pneumoniae carriage and search for new diagnostic approaches for etiological interpretation of S. pneumoniae-associated diseases.